Friction Coefficient of Rubber Shoe Sole Sliding Against Different Rubber Floor Tiles - Mohamed Ahmed Ramadan (Tribology in Industry, 2022)
Slips and falls can occur in any part of the flat, workshop, outside the pool, or gym, but they are more common in children's areas with lots of movement. The friction between different types of floor tiles and rubber footwear is investigated in this study. The tests were conducted with particular test rig that could measure the friction coefficient between the shoe sole and rubber tiles. The tests were carried out by sliding the shoe sole against three different types of commercial rubber tiles (floors) under three different conditions (dry, mixture of water & soap and paraffin oil). Surfer13 software was used to analyze the surface texture of the flooring samples, which processed and converted the images into a 3D surface map. The data of 2d surface profile was imported into Origin software and the surface roughness data was calculated. COF results were compared to the standards safety guidelines. This study yielded important tribological findings that could help to guide the approach to reducing indoor slips and falls injuries. Based on findings, the friction coefficient has affected by lubrication on the contact surface, Surface texture of the contact surfaces, Surface roughness and normal load through the sliding. The investigation findings might serve as guidance for preventing slip and fall injuries. The surface roughness data obtained by digital image processing was in a good agreement with that obtained by conventional roughness testing machine.